White Spot Syndrome Virus-Induced Shrimp miR-315 Attenuates Prophenoloxidase Activation via PPAE3 Gene Suppression - Jaree, Phattarunda; Wongdontri, Chantaka; Somboonwiwat, Kunlaya (Frontiers in Immunology, 2018)
MicroRNAs (miRNAs), the small noncoding RNAs, play a pivotal role in posttranscriptional gene regulation in various cellular processes. However, the miRNA function in shrimp antiviral response is not clearly understood. This research aims to uncover the function of pmo-miR-315, a white spot syndrome virus (WSSV)-responsive miRNAs identified from Penaeus monodon hemocytes during WSSV infection. The expression of the predicted pmo-miR-315 target mRNA, a novel PmPPAE gene called PmPPAE3, was negatively correlated with that of the pmo-miR-315. Furthermore, the luciferase assay indicated that the pmo-miR-315 directly interacted the target site in PmPPAE3 suggesting the regulatory role of pmo-miR-315 in PmPPAE3 gene expression. Introducing the pmo-miR-315 into the WSSV-infected shrimp caused the reduction of the PmPPAE3 transcript level and, hence, the PO activity activated by the PmPPAE3 whereas the WSSV copy number in the shrimp hemocytes was increased. Taken together, our findings state a crucial role of pmo-miR-315 in attenuating proPO activation via PPAE3 gene suppression and facilitating the WSSV propagation in shrimp WSSV infection.